Association between pregnancy intention and completion of newborn and infant continuum of care in Sub-Saharan Africa: systematic review and meta-analysis - Birye Dessalegn Mekonnen; Vidanka Vasilevski; Ayele Geleto Bali; Linda Sweet (BMC, 2024)
Abstract Background The newborn and infant continuum of care such as essential newborn care, early initiation and exclusive breastfeeding, and immunisation are highly recommended for improving the quality of life and survival of infants. However, newborn and infant mortality remains high across Sub-Saharan African countries. While unintended pregnancies are associated with adverse newborn and infant health outcomes, there is inconclusive evidence on whether pregnancy intention influences newborn and infant continuum of care completion. Therefore, this review aimed to pool findings reported in the literature on the association between pregnancy intention and newborn and infant health care across the continuum of care in Sub-Saharan Africa. Methods We searched MEDLINE Complete, EMBASE, CINAHL Complete, and Global Health databases for studies potentially eligible for this systematic review and meta-analysis. Two researchers independently screened the identified articles by abstract and title, and then full-text using Covidence. We used the Newcastle-Ottawa Scale to assess the quality of the included studies. The Cochran's Q test and I2 were executed to detect and quantify the presence of statistical heterogeneity in the studies. Meta-analysis was done for each outcome when more than one original study reported relevant data, using Stata statistical software version 18. Results Eleven studies were included from a total of 235 articles identified by the search. The odds of completing essential newborn care (pooled odds ratio: 3.04, 95% CI: 1.56, 5.90), early initiation of breastfeeding (pooled odds ratio: 1.30, 95% CI: 1.13, 1.52), exclusive breastfeeding (pooled odds ratio: 2.21, 95% CI: 1.68, 2.89), and being fully immunised (pooled odds ratio: 2.73, 95% CI: 1.16, 6.40) were higher among infants born to women with intended pregnancies as compared to women with unintended pregnancies. Conclusion Intended pregnancy was positively associated with essential newborn care completion, early initiation and exclusive breastfeeding, and full immunisation of infants in SSA countries. Thus, policy-makers and stakeholders should strengthen the provision of quality family planning services to prevent unintended pregnancy. Furthermore, follow-up of women with unintended pregnancies is needed to increase women's opportunity to access essential newborn health care services that further reduce the risk of newborn and infant morbidity and mortality. Systematic review registration PROSPERO registration number CRD42023409148.